PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP PENGELOLAAN KEUANGAN DAERAH SERTA KINERJA PEMERINTAH DAERAH - Pujiono, Dodik Slamet; Sukarno, Hari; Puspitasari, Novi (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract:This study aimed to analyze the effect of: (1) internal control system on the local financial management, (2) internal control sistem on the performance of local government, and (3)local financial management on the performanceof local government.The population was the leaders and heads of the Finance Department of Local Government in North Maluku Province. The samples were consisted of 80 respondents. Path analysis with Confirmatory Factor Analysis was employed as the method of analysis. The results showed that: (1) internal control sistem significantly affects the local financial management in North Maluku, (2)internal control sistem significantlyaffects local government performance of North Maluku, and (3) local financial management significantly affects the performance of local government of North Maluku Province. Keywords: Internal Control, Local Finance Management, and Performance of Local Government.